2011
DOI: 10.1007/s13312-012-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin as a marker of complications in type I diabetes

Abstract: Elevated adiponectin level in children and adolescents with type I diabetes indicates poor glycemic control and development of complications, especially nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…There were similar observations in obese diabetic boys in an earlier study published in Indian Pediatrics [7]. In this issue of the journal, Habeeb, et al provide another observation of adiponectin as a marker for complications in children with T1DM [8].…”
supporting
confidence: 65%
“…There were similar observations in obese diabetic boys in an earlier study published in Indian Pediatrics [7]. In this issue of the journal, Habeeb, et al provide another observation of adiponectin as a marker for complications in children with T1DM [8].…”
supporting
confidence: 65%
“…Conversely, adiponectin levels correlate negatively with visceral and subcutaneous fat areas [62, 63] with low adiponectin levels associated with obesity, type 2 diabetes, and insulin resistance [59]. An increased level of adiponectin was found in diabetic and nondiabetic subjects with impaired kidney function as well as in type 1 diabetic patients without complications and particularly in those with diabetic nephropathy [6265]. In our study, there were no statistically significant differences in BMI between, the investigated groups according to DR status.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, another study showed that, serum adiponectin level in patients with poor glycemic control is higher than in patients with good glycemic control and has direct association with HbA 1 % in type 1 diabetics, so it can be used as a good marker for metabolic state among these patients [ 8 ]. Also other studies found such correlation with the HbA 1 % [ 4 , 24 ]. A study done by Wang et al, [ 25 ] put an explanation for the effect of glycemic control on serum adiponectin levels.…”
Section: Discussionmentioning
confidence: 57%